Healthy lifestyle behavior and risk of long duration troublesome neck pain or low back pain among men and women: results from the Stockholm Public Health Cohort - Skillgate, Eva (Clin Epidemiol, 2017)
BACKGROUND: The role of healthy lifestyle behavior (HLB) in terms of physical activity, alcohol intake, smoking, and diet put together has not yet been explored for the risk of low back pain (LBP) and neck pain (NP). Our aim was to study if an HLB is protective against the onset of long duration troublesome LBP and NP in men and women. METHODS: Two cohorts from the Stockholm Public Health Cohort, free from LBP (n=12,483) and NP (n=10,539), respectively, in 2006, were surveyed with questionnaires. Baseline information about physical activity, alcohol intake, diet, and smoking were dichotomized into being healthy/not healthy and combined in a categorical variable according to the number of healthy behaviors present. Binomial regression analyses were used to evaluate the role of HLB for the outcomes 4 years later. RESULTS: When men with three or four healthy lifestyles were compared to men with none or one, the risk ratio (RR) of LBP was 0.63 (95% confidence interval [CI]: 0.39–1.02). The corresponding RR for LBP in women was 0.86 (95% CI: 0.56–1.32). When men with three or four healthy lifestyles were compared to men with none or one, the RR for NP was 1.13 (95% CI: 0.74–1.71). The corresponding RR for NP in women was 0.52 (95% CI: 0.35–0.77). CONCLUSION: An HLB seems to be protective for long duration troublesome LBP in men, and for long duration troublesome NP in women.